Antioxidant, phase II and III responses induced by lipoic acid in the fish Jenynsia multidentata (Anablapidae) and its influence on endolsulfan accumulation and toxicity - Monserrat, José María (2013)
Antioxidants like lipoic acid (LA) are known to trigger augmented antioxidant and phase II and III responses. This study aimed to evaluate the effect of LA in P-glycoprotein (Pgp) expression, glutathione-S-transferase (GST) activity, total antioxidant competence, levels of lipid peroxides (TBARS) and accumulation of the organochlorine insecticide endosulfan (Endo: α-, β-isomers and sulfate metabolite) in different organs of the fish Jenynsia multidentata. One hundred and twenty females (1.55 ± 0.07 g) were fed during 8 days with (n = 60) or without (n = 60) a LA enriched ration (6000 mg/kg). Four experimental groups were defined: −LA/−Endo; +LA/−Endo; −LA/+Endo; and +LA/+Endo. Endo groups were exposed during 24 h to 1.4 μg of insecticide/L. Results showed that only LA induced a significant increment in liver Pgp expression. GST activity was augmented in liver after exposure to LA or Endo. TBARS levels were lowered in liver and gills after LA pre-treatment. Total antioxidant capacity was lowered in liver of Endo exposed fish, a result that was reversed by LA pre-treatment. It is concluded that LA induced the expected effects in terms of Pgp expression, GST activity and reduced TBARS levels although favored α-Endo accumulation in brain. However, the Endo metabolism to the more persistent endosulfan sulfate was not facilitated by LA pre-treatment.